Answer:
x = -4
Explanation:
Solve for x:
(5 x)/4 = x/2 - 3
Put each term in x/2 - 3 over the common denominator 2: x/2 - 3 = x/2 - 6/2:
(5 x)/4 = x/2 - 6/2
x/2 - 6/2 = (x - 6)/2:
(5 x)/4 = (x - 6)/2
Multiply both sides by 4:
(4×5 x)/4 = (4 (x - 6))/2
(4×5 x)/4 = 4/4×5 x = 5 x:
5 x = (4 (x - 6))/2
4/2 = (2×2)/2 = 2:
5 x = 2 (x - 6)
Expand out terms of the right hand side:
5 x = 2 x - 12
Subtract 2 x from both sides:
5 x - 2 x = (2 x - 2 x) - 12
5 x - 2 x = 3 x:
3 x = (2 x - 2 x) - 12
2 x - 2 x = 0:
3 x = -12
Divide both sides of 3 x = -12 by 3:
(3 x)/3 = (-12)/3
3/3 = 1:
x = (-12)/3
The gcd of -12 and 3 is 3, so (-12)/3 = (3 (-4))/(3×1) = 3/3×-4 = -4:
Answer: x = -4